PENGARUH LITERASI KEUANGAN, STATUS SOSIAL EKONOMI ORANG TUA , DAN PENDAPATAN UANG SAKU TERHADAP PENGELOLAAN KEUANGAN MAHASISWA (STUDI KASUS PADA MAHASISWA PRODI AKUNTANSI UNIVERSITAS MALAHAYATI ANGKATAN 2023) - Alansori, Afif; Barsah, Alpinka; Ghilba, Sakila El; Wulandari, Siti Ayu (Jurnal Ilmiah Akuntansi Rahmaniyah, 2025)
This study aims to determine the influence of financial literacy, socioeconomic status, and pocket income on student financial management. The method used is a qualitative approach with semi-structured interview techniques and an open questionnaire to 50 students of the Accounting Study Program Class of 2023 at Malahayati University Bandar Lampung. The results of the study show that these three variables have an influence on student financial management behavior. Students with good financial literacy tend to be able to budget and manage expenses wisely. The socioeconomic status of the family also shapes the financial stability of students through the financial support provided. In addition, a sufficient allowance income encourages students to plan their finances better, although the amount of allowance does not necessarily guarantee effective management skills. The limitations in this study lie in the limited scope of respondents and have not considered other variables such as lifestyle or the influence of the social environment. This research contributes to enriching the understanding of factors that affect student financial management and can be an input for the campus and parents in supporting the financial literacy of the younger generation.